3rd Arctic Science Ministerial Report - Knowledge for a Sustainable Arctic (Icelandic Ministry of Education, Science and Culture, 2021)
To strengthen international cooperation and respond to the severe threat of climate change and biodiversity loss in the Arctic, the Icelandic Ministry of Education, Science and Culture and the Japanese Ministry of Education, Culture, Sports, Science and Technology co-organized the 3rd Arctic Science Ministerial (ASM3) which was held in Tokyo on 08-09 May 2021. Delegates from 27 different countries and the European Commission, as well as representatives from Arctic Indigenous Peoples’ Organizations, gathered in Tokyo and online to discuss developments in international research and commit to future cooperation. This meeting was built on the themes initiated by the first Arctic Science Ministerial hosted by the United States and held in Washington, D.C. in 2016, and the second Arctic Science Ministerial co-hosted by the European Commission, Finland and Germany and held in Berlin in 2018. Knowledge for a Sustainable Arctic was the overarching theme for ASM3 and included four sub-themes under the titles: Observe, Understand, Respond, Strengthen. These reflect elements of the previous ASM themes and reintroduce an emphasis on education which appeared in the first Ministerial.